Intermittent Fasting: A Promising Tool for Controlling Diabetes - Krishna, Ambati Vamsi; Gandodi, Vedavathi Sai; Dev, Apoorva; Chakravarthy, Adusumalli; Vidyadhara, Suryadevara; Begum, Shaik Shafiya (Indian Journal of Pharmacy Practice)
Intermittent fasting has gained attention as a potential strategy for managing diabetes mellitus, a common metabolic condition characterized by low insulin sensitivity or insufficient insulin synthesis. This article offers a thorough analysis of the benefits, dangers, and consequences of intermittent fasting for the control of diabetes. It discusses the metabolic impacts of intermittent fasting on insulin levels, insulin resistance, and glucose control, drawing insights from both animal and human studies. The article also highlights the importance of careful consideration and medical supervision, especially for individuals with type-1 or type-2 diabetes, due to the potential risk of hypoglycemia and other adverse effects. The limited yet promising evidence suggests that using intermittent fasting can help us loss weight. Reduced insulin requirements, and improved glycemic control. However, caution is advised, and personalized adjustments to diabetes medications and monitoring of blood glucose levels are essential to ensure the safety and efficacy of intermittent fasting as part of diabetes management.
Keywords: Diabetes; Intermittent fasting; Consequences; Investigation; Implementation; Medications; Hypoglycemia; Insulin; Medical Intervention